2011
DOI: 10.1002/hed.21716
|View full text |Cite
|
Sign up to set email alerts
|

Parafibromin immunohistochemical staining to differentiate parathyroid carcinoma from parathyroid adenoma

Abstract: Loss of parafibromin immunostating showed promising results in the differential diagnosis of parathyroid carcinoma from adenoma and may also serve as a prognostic marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 31 publications
1
25
0
2
Order By: Relevance
“…Recently, parafibromin, a protein encoded by the HRPT2. Its expression level is decreased or absent in PC in contrast to PA and PH in which HRPT2 expression is retained [21]. In our case, parafibromin expression was decreased in PC and not in PH, and this finding was consistent with the previous study.…”
supporting
confidence: 93%
“…Recently, parafibromin, a protein encoded by the HRPT2. Its expression level is decreased or absent in PC in contrast to PA and PH in which HRPT2 expression is retained [21]. In our case, parafibromin expression was decreased in PC and not in PH, and this finding was consistent with the previous study.…”
supporting
confidence: 93%
“…Diffuse or focal loss of nuclear parafibromin expression by immunohistochemistry has been found in the majority of parathyroid carcinomas but very rarely in parathyroid adenomas. 49,51,52,[64][65][66][67][68][69][70] A recent genome-wide study of DNA methylome from benign and malignant parathyroid tumors identified a number of genes with altered DNA methylation patterns independent of the tumor's nature, suggesting that other genes are involved in parathyroid carcinogenesis. 71 Costa-Guda et al have recently shown that allelic loss at chromosome 11q, the most common alteration in parathyroid adenomas, has never been detected in parathyroid cancers, suggesting that parathyroid malignancy arises de novo, rather than evolving from a pre-existing benign lesion.…”
Section: Pathogenesismentioning
confidence: 98%
“…Histological differences are useful for the differential diagnosis, such as the criteria for malignancy proposed by Schantz and Castleman [4]: 1) the presence of a trabecular growth pattern, mitotic figures, and capsular or vascular invasion; and 2) the presence of nodal or distant metastasis. Recently, loss of parafibromin immunostaining helped with the differential diagnosis of parathyroid carcinomas from adenomas in Asians and may serve as a prognostic marker in patients with parathyroid carcinomas [5]. In our case, the left parathyroid mass exhibited capsular invasion with extension into the adjacent soft tissue and trabeculum, clear cytoplasm, and atypical nuclei with atypical mitoses, suggesting carcinoma.…”
mentioning
confidence: 65%
“…The most effective treatment of parathyroid carcinoma is complete removal of the primary lesion during surgery [1,5]. If patients with benign adenomas or hyperplasia are suspected of having concurrent parathyroid carcinoma, the surgeon should explore all four parathyroid glands.…”
mentioning
confidence: 99%